Carbon dioxide emission savings potential of household water use reduction in the UK. - GRAY, NICHOLAS FREDERICK (ccsenet.org, 2009)
The relationship between household water use and energy consumption was examined to establish whether the conservation of water within a domestic environment offers significant potential for saving energy, thereby reducing household carbon dioxide emissions. Average UK water usage is 55,121 L ca-1yr-1. The supply of this volume of water and its subsequent treatment by the water companies is equivalent to just 38.6 kg CO2 ca-1 yr-1, although this is not currently included in the primary footprint. So water consumption per se does not significantly effect CO2emissions. However, the heating water within the household using electricity requires 5,036 kWh ca-1yr-1, equivalent to a further 2,830 t CO2 ca-1yr-1 with 57% of energy associated with use of heated tap water. Using gas instead of electricity to heat water can reduce emissions by 63%, equivalent to an average reduction of 4.36 t CO2 yr-1 for a standard household (2.4 occupants). Water efficient appliances and the careful use of heated water in the home could reduce average household water use from 151 to 73 L ca-1d-1 as well as the volume of water required to be heated thereby reducing related emissions by 58% or 1,662 kg CO2 ca-1yr-1, where electricity is used. Maximum CO2 emission reduction is achieved by the use of solar collectors using gas as standby heating fuel. This, coupled with simple water conservation measures, emits as little as 130 kg CO2 ca-1yr-1 a potential saving of 2.7 t CO2 ca-1yr-1.
PUBLISHED
Keywords: Carbon emissions; Water supply